Pengembangan Pendidikan Karakter di RA Bina Insani Muslim Selama Pandemi Covid-19 - mia fitriah elkarimah (SAP (Susunan Artikel Pendidikan), 2021)
Character education is an important provision in preparing early childhood in facing a future full of challenges, both academically and in the life of the nation and state, learning at Roudhotul Athfal Bina Ibsani Muslim in the current conditions of the Covid-19 pandemic is a challenge in efforts to manage education character even though the intensity of the encounter between teachers and students is reduced and moves to digital spaces. This study aims to describe the development of character education in RA Bina Insani during the Covid-19 pandemic. This research instrument uses observation, semi-structured interviews where the researcher tries to open the opinion and ideas of the informants so that the problem becomes clear. The technique used to analyze the data used a qualitative descriptive technique. The results showed that there are four models of learning model RA Bina Insani Muslimi during the Covid-19 pandemic; Online (online), offline (offline), Home visit (home learning once a week) and School Visit. The results show that the development of character education is outlined in daily and weekly programs and is still escorted by teachers by providing character control sheets, and providing appreciation and guidance for those who do not meet the criteria. The characters developed are the child's personality, independence, discipline, and responsibility.